RISK FACTORS OF URETHRAL STRICTURE: A SYSTEMATIC REVIEW - Andhika S, Teguh (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
Background: Urethral stricture in males is a narrowing of the anterior urethra caused by fibrosis and cicatrisation of the urethral mucosa and adjacent spongiosus tissue ("spongiofibrosis"). In the male posterior urethra, there is no spongiosus tissue; therefore, stenosis is the preferred term. Understanding the risk factors of urethral strictures may be amenable to preventive measures resulting in a decrease in disease severity and health care expenditure. Aim: This study aims to summarize and assess the risk factors of urethral stricture through a comprehensive systematic review. Methods: A systematic search strategy was conducted across several electronic reference databases (PubMed, Cochrane Library, Google Scholar) and included articles published between 2013–2023. Duplicate publications, review articles, and incomplete articles were excluded. Results: The databases search identified a total of 16.645 articles (Table 1) and resulted in 16.155 articles after duplicates removed. Of these, 15.955 articles were excluded due to non-original study and titles and abstract not represented the focus of interest; and resulting in 200 articles for screening process. Articles not evaluating the focus of interest and articles in which full-text are not available are excluded, resulting in 15 articles for eligibility criteria. Among them, 10 articles did not give sufficient details about the risk factors of urethral stricture and some did nit differenriate clearly between the risk factors of urethral stricture and recurrence of urethral stricture. Hence, we found 5 appropriate studies included. Conclusion: The risk factors of urethral stricture in this study includes the dose of brachyterapy for prostate cancer patients, lower resection speed of BPH, prolonged operative time, intraoperative urethral mucosa rupture, post-operative continuous infection, the diameter of the instrument, presence of chronic prostatitis in anamnesis, increased volume of the prostate, repeated drainage of the bladder using the urethral catheter, high comorbidity burden, second TURP surgery, history of preoperative catheter insertion, high postoperative WBC, and long postoperative catheterization time.